Analisis Fundamental terhadap Saham Syariah dalam Memutuskan Berinvestasi di Saham yang Listing di Indeks Saham Syariah Indonesia - Arfa Arfa; Budi Efriadi (AL-Muqayyad, 2022)
The purpose of this article is to find out the fundamental analysis of the Indonesian Sharia Stock Index by observing and observing stock price movements. This type of quantitative research uses secondary data, financial statement analysis is taken through the official website www.idx.co.id. Data analysis using the Simple Moving Average and Relative Strength Index methods, with the approach of Price Earning Ratio (PER) and Price Book Value (PBV). The data is used in 2016-2019 as the object of research on Xl Axiata shares and Indofood CBP Sukses Makmur shares. The results of Indonesia's macroeconomic fundamental analysis provide a positive signal for investing in the 2016-2019 period in the Indonesian capital market. Analysis of financial ratios, XL shares have a negative signal for investment, XL shares intrinsic value is smaller than the market price so that it is said to be overvalued shares based on the PBV method. While ICBP shares provide a positive picture for investment based on the intrinsic value of ICBP shares which is also higher than the market price, it is said to be undervalued shares worth buying based on the PER method, ICBP shares have fairly good financial ratios seen from effective and efficient liquidity, solvency and profitability ratios.